Ontologies for the semantic web - Vallés, María Clara (2008)
The Semantic Web attempts to reach a state in the future where everything on the Web will no longer be only machine-readable, but also machine-understandable. An ontology is an explicit specification of a conceptualization. A conceptualization is an abstract, simplified view of the world that we wish to represent for some purpose. Every knowledge base, knowledge-based system, or knowledge-level agent is committed to some conceptualization, explicitly or implicitly. By defining shared and common domain theories, ontologies help both people and machines to communicate concisely, supporting the exchange of semantics and not only syntax. Hence, the construction of domain- specific ontologies is crucial for the success and the proliferation of the Semantic Web.